Effect of electron irradiation on electric transport properties of aromatic self-assembled monolayers - Yildirim, Can; Sauter, Eric; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
We studied the effect of electron irradiation on electric transport properties of aromatic thiolate self-assembled monolayers (SAMs) with oligophenyl (OPh), acene, and oligo(phenylene ethynylene) (OPE) backbones of variable length. The resistance of these SAMs was found to increase progressively, by 2-3 orders of magnitude upon irradiation with doses up to 40 mC/cm2. The electric transport properties of the irradiated SAMs could be well described by the simplified Simmons’ equation, with the attenuation factor (β) and contact resistance (R0) as parameters. The β value decreased moderately for the OPh and OPE films but increased slightly for the acene monolayers upon irradiation. The R0 value increased significantly upon irradiation for all three types of SAMs and was considered as the major reason for the observed increase in the total resistance of these films. In its turn, the increase in R0 was attributed to the combined effect of a partly deteriorated anchoring to the substrate at the SAM-substrate interface and progressive irradiation-promoted adsorption of airborne molecules at the SAM-ambient interface. The effect of the work function, studied in the given context as well and exhibiting a small change only upon irradiation, is believed to be of negligible influence on R0. Finally, for the three-ring systems, the transition voltage (Vtrans) could be monitored. It showed progressive decrease upon irradiation for all three kinds of aromatic backbones. This behavior was considered as a fingerprint for the decrease in the width of the HOMO-LUMO gap upon irradiation, which can be potentially useful for bandgap engineering.
Publication Date (Web): March 16, 2017
Gesehen am 03.07.2018